a, 3x^2-6x+2xy-4y
b, a^2(a^2+4)-a^2+4
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(a,=x\left(x^3+3x^2-6x-8\right)\\ =x\left(x^3+4x^2-x^2-4x-2x-8\right)\\ =x\left(x+4\right)\left(x^2-x-2\right)\\ =x\left(x+4\right)\left(x-2\right)\left(x+1\right)\)
\(b,=x^4+36x^2+324-36x^2\\ =\left(x^2+18\right)^2-36x^2\\ =\left(x^2+6x+18\right)\left(x^2-6x+18\right)\)
\(c,=xy\left(x^3y^3+xy+2\right)\)
\(a,3x\left(3x+6\right)=9x^2+18x\)
\(b,-\dfrac{1}{2}xy\left(4x^2+6x\right)\)
\(=-2x^3y-3x^2y\)
\(c,-2x^2y^3\left(\dfrac{1}{2}xy+4y^2\right)\)
\(=-x^3y^4-8x^2y^5\)
\(d,-6x^2\left(\dfrac{1}{3}xy^2-\dfrac{1}{2}y\right)\)
\(=-2x^3y^2+3x^2y\)
#\(Urushi\)
\(a.=-4\left(x^2-2x+1\right)\)
\(=-4\left(x-1\right)^2\)
\(b.=3x\left(x-2\right)+2y\left(x-2\right)\)
\(=\left(3x+2y\right)\left(x-2\right)\)
2xy - x2 - y2 + 36=-(x2-2xy+y2-36)=-(x-y)2-36=-(x-y-6)(x-y+6)
a: \(=\left(-\dfrac{6}{2}\right)\cdot\dfrac{x^3}{x}\cdot\dfrac{y^2}{y^2}=-3x^2\)
b: \(=\left(-\dfrac{1}{4}:\dfrac{1}{2}\right)\cdot\dfrac{x^4}{x^3}\cdot\dfrac{y^3}{y^2}=-\dfrac{1}{2}xy\)
c: \(=\dfrac{8}{4}\cdot\dfrac{x^4}{x^3}\cdot\dfrac{y^5}{y^4}=2xy\)
a: \(=2x^6-x^5-\dfrac{1}{3}x^4\)
b: \(=4xy^2-x^3+y^2-\dfrac{3}{4}x^2y\)
c: \(\left(3x^3-2xy^3+4y^2\right)\cdot\left(\dfrac{1}{6}x^2y^2\right)\)
\(=\dfrac{1}{2}x^5y^2-\dfrac{1}{3}x^3y^5+\dfrac{2}{3}x^2y^4\)